CATEGORY MANAGEMENT AS A STRATEGIC APPROACH TO PRODUCT ASSORTMENT MANAGEMENT - SHARKO, Vitalii; HAVENKO, Mykhailo; KRYVESHCHENKO, Viktoriya (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Currently, in search of sources of competitive advantages, most retail businesses are increasingly revising the conditions of their internal business organization, which is based on the implementation of category management technologies. The aim of the article is to explore the concept of category management, establish the key components and advantages and disadvantages of category management for retail enterprises, and develop criteria for the readiness of a business to implement a category management algorithm for retail companies; the development of a structural scheme of interaction between business partners in the process of implementing tactical decisions for product categories. Category management in retail enterprises is one of the effective areas that must be clearly defined and implemented in order to reach the level of ideal business in trade. The paper presents the results of a study of the essence of the concepts of "category management" and "product categories". The advantages and disadvantages of category management in a retail enterprise are analyzed. An algorithm for managing product categories is proposed. A scheme for the interaction of trading partners in the process of implementing tactical solutions for a product category in terms of the components of the marketing complex is developed. A number of stages for stimulating sales in accordance with this industry are determined. It is found that the practical value of category management lies in the fact that it is a consumer-oriented marketing technology for managing the movement of goods, which allows you to combine the organizational, strategic and operational cycle. At the same time, it is necessary to develop, plan, and implement a range of goods in order to optimize sales and profits, and create maximum conditions for trade service for a potential client.